Pengaruh Metode Make a Match Berbantu Media Flashcard terhadap Penguasaan Kosakata Siswa SD Negeri Peninggilan 01 - Padyah, Padyah; Sa’odah, Sa’odah; Nurfadillah, Septy (ANWARUL, 2022)
This study aims to determine the use of assisted flashcard match media has a significant effect on students' vocabulary mastery of body parts in grade 3 students at Peninggilan 01 State Elementary School. There will be hypothesis testing using t test at the end of learning (posttest) in the control class and experimental class. obtained tcount = 3.25 using a significance level of 95% (∞ = 0.05) obtained ttable = 2.001 because 3.25> 2.001 (tcount> ttable) then Ho is rejected. using this at the end of the lesson various learning differences of the student classes between the control and experimental classes. using it according to what will happen in research that has been done that the method of making flashcard media matches has an effect and increases students' vocabulary mastery. Its application in the classroom can produce students to play an active and creative role.